Biopolymer enhanced vegetation establishment and their coupled effects on soil hydro-mechanical properties - Jiayu Gu; Junjun Ni; Yanbo Chen; Yufeng Gao (Soil and Tillage Research, 2026)

Bio-based modification of recycled concrete aggregate for cover systems: eco-hydro-mechanical performance evaluation - Jiayu Gu; Jingsong Zhou; Junjun Ni; Muhammad Qasim; Saif Ullah (Waste Management, 2026)

Hydro-mechanical properties of biochar-amended cracked soils and their impact on slope stability with reliability analysis - Siqing Yang; Junjun Ni; Jiayu Gu (Bulletin of Engineering Geology and the Environment, 2026)

Molecular dynamics study on the pyrolysis and soot formation mechanisms of benzyl phenyl ether - Wenjing Luo; Jian Yi; Jianmin Gu; Junjiang Guo; Junjun Wu; Hongbo Ning (Fuel, 2026)

Experimental and DEM investigation of thermal effects on mechanical properties of biopolymer treated soil - Jiayu Gu; Junjun Ni; Guizhong Xu; Yanhui Zhou; Haoyu Zhang (Transportation Geotechnics, 2026)

Clinical Values of Serum Extracellular Vesicle MicroRNA Profiles as Molecular Biomarkers for Ischemic Stroke and Transient Ischemic Attack - Xinran Wu; Zhuoying Gu; Chenxi Kong; Xueqin Jiang; Qianqian He; Ziwu Han; Jia Wu; Junjun Wang (Molecular Neurobiology, 2026)

The effects of dietary astaxanthin on the intestinal microbiota and metabolites, antioxidant capacity, and resistance to Decapod iridescent virus 1 in Macrobrachium rosenbergii - Cui Liu; Qiusheng Jing; Li Wang; Qincheng Huang; Yukun Jie; Yutong Zheng; Tiantian Ye; Junjun Yan; Zhimin Gu (Fish & Shellfish Immunology, 2025)

Shear strength of biopolymer amended soil under freeze-thaw cycles: Experimental investigation and DEM modeling - Jiayu Gu; Junjun Ni; Shusen Liu; Yanbo Chen (Engineering Geology, 2025)

Suppressing sediment nutrient release via electrokinetic drainage of porewater: apparent paradox and underlying mechanisms - Danyang Wang; Xianqiang Tang; Rui Li; Yanping Hu; Junjun Gu; Zhenhua Wang (Journal of Environmental Management, 2025)

Influence of biopolymer-vegetation interaction on soil hydro-mechanical properties under climate change: A review - Yifei Liu; Junjun Ni; Jiayu Gu; Shusen Liu; Yi Huang; Hamed Sadeghi (Science of The Total Environment, 2024)

Highly efficient adventitious root regeneration and Agrobacterium rhizogenes-mediated hairy root transformation in pear - Cheng Xue; Liyan Chang; Junjun Liu; Kaidi Gu; Pengfei Zheng; Jun Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

Carbon felt (CF) acted as an “ionic capacitor” to enhance flow electrode capacitive deionization (FCDI) desalination performance - Yunke Li; Junjun Ma; Minghao Yu; Jianrui Niu; Jiarong Gu; Meng Chen; Puming Zhang; Jing Zhang; Chun Liu (Desalination, 2024)

A hypoplastic model for unsaturated sand accounting for drying and wetting cycles - Junjun Ni; Jiayu Gu; Xudong Zhao (Computers and Geotechnics, 2024)

Preparation of dual-functional packaging films containing green tea essential oil microcapsules for strawberry preservation: Excellent barrier properties and antioxidant activity - Weijie Zhao; Lianjun Yu; Yali Gu; Weijia Ma; Kehui Wang; Junjun Liang; Qi Liu (Food Bioscience, 2023)

Müller Glia Cells Activation in Rat Retina After Optic Nerve Injury: Spatiotemporal Correlation with Transcription Initiation Factor IIB - Yue Xu; Chen Chen; Nan Jin; Juming Zhu; Lihua Kang; Tianqiu Zhou; Junjun Wang; Aiqin Sheng; Jian Shi; Zhifeng Gu; Aimin Sang (Journal of Molecular Neuroscience, 2013)

Involvement of transcription initiation factor IIB in the light-induced death of rat retinal ganglion cells in vivo - Aimin Sang; Yue Xu; Nan jin; Tianqiu Zhou; Junjun Wang; Juming Zhu; Chen Chen; Jian Shi; Jie Shuai; Guofeng Xu; Zhifeng Gu (Journal of Molecular Histology, 2013)

Plus- and minus-stranded foot-and-mouth disease virus RNA quantified simultaneously using a novel real-time RT-PCR - Chaojiang Gu; Congyi Zheng; Lili Shi; Qian Zhang; Yong Li; Bin Lu; Yi Xiong; Sanpu Qu; Junjun Shao; Huiyun Chang (Virus Genes, 2007)